Низкорейнольдсовая модель турбулентности с ограничителем производства кинетической энергии - Ершов, Сергей Владимирович; Деревянко, А. И. (НТУ "ХПИ", 2010)
The Low–Reynolds turbulence model with the kinetic energy production limiter is considered. The laminar-turbulent transition method is implemented in the solver FlowER-Y on the base of the k–ω SST model. The results of the calculations were compared with experimental data from ERCOFTAC database for gas flow along a flat plate. It is shown that the low-Reynolds modification of the k–ω SST model allows an approximate simulation of a transitional flow
Keywords: турбомашины; турбины низкого давления; осредненное турбулентное течение